2016
DOI: 10.1007/s10661-016-5264-9
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation kinetics, safety evaluation, and preharvest interval assessment of trichlorfon application on rice

Abstract: Nowadays, there is an urgent need for the investigation of the field dissipation and assessment of the preharvest interval for trichlorfon residues on rice. To protect consumers from potential health risks, this study can provide references for the safe application of trichlorfon in the rice fields. Results of the field dissipation study showed that the dissipation dynamic equations of trichlorfon were based on the first-order reaction dynamic equations and that the dissipation rates vary among rice plant, bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Superoxide dismutase and CAT are important antioxidant enzymes, and are scavengers of ROS. The activation of SOD and CAT constitutes the first line of defensive against oxidative stress ( Ken et al, 2005 ; Singh et al, 2016 ). SOD catalyzes the conversion of superoxide radicals to hydrogen peroxide, while CAT converts hydrogen peroxide into water ( Mansour and Mossa, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superoxide dismutase and CAT are important antioxidant enzymes, and are scavengers of ROS. The activation of SOD and CAT constitutes the first line of defensive against oxidative stress ( Ken et al, 2005 ; Singh et al, 2016 ). SOD catalyzes the conversion of superoxide radicals to hydrogen peroxide, while CAT converts hydrogen peroxide into water ( Mansour and Mossa, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, after occupational or accidental exposure to trichlorfon residues, humans have suffered reproductive, mutagenic and carcinogenic toxicity ( Fernandes et al, 2015 ; Yonar et al, 2015 ). Thus, in some countries such as the United States, trichlorfon is registered for non-agricultural uses, such as animal kennels, ornamental shrubs and plants, and is also registered for indoor non-food use ( Chen et al, 2016 ). However, trichlorfon is still extensively used in agriculture on a global scale, and its product volume is even increasing in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the SFOK model was used to derive the dissipation parameters for IMI, THI, and THX. Similarly, most researchers have used the SFOK model to predict the dissipation kinetics of different pesticides in various plants (Torabi and Talebi 2013;Ugare et al 2013;Hwang et al 2015;Ramezani and Shahriari 2015;Chen et al 2016;Alister et al 2017;Hwang et al 2018). A few research have also shown the bi-phasic pattern of pesticide dissipation in plants (Utture et al 2011;Memarizadeh et al 2019).…”
Section: Uptake and Dissipation Kinetics Of Pesticides In Pistachio Nutsmentioning
confidence: 99%
“…These distribution processes result in decreased pesticide levels in sap water compared to the outside surface concentrations, which will keep the driving force for passive uptake of the chemicals until reaching the partition limit (e.g., an equilibrium) (Liu et al 2021). Also, several exponential decay models, including the simple first-order kinetic (SFOK), zero-order (ZO), second-order (SO), and first-order double-exponential decay (FODED), have been utilized to predict the dissipation trends of agrochemicals in crops (Utture et al 2012;Torabi and Talebi 2013;Rahimi et al 2015;Ramezani and Shahriari 2015;Chen et al 2016;Alister et al 2017;Torabi et al 2017;Lee et al 2019). SFOK, ZO, and SO are log-linear models which consider pesticide dissipation a mono-phasic process with a single rate constant (see Eqs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation